Adoption of Technology and Digital Marketing Innovation for the Development of Coffee Production and the Economy of Prohutani Tawangmangu Coffee Farmer Group - Reni Shinta Dewi; Dhaifina Idznitia Apriyani Naimi; Wildan Avian Pratama; Chatrine Cahaya Mykino,; Syifa Salina; Putra Versa Maulana Amir; Rizkia Ramadhani Andoko; Surya Adi Wijaya Aritonang; Pinkan Viviana Devy (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study evaluated adoption of postharvest technologies and digital marketing among Prohutani Tawangmangu coffee farmers to address quality loss, limited market access, and low incomes, and to assess impacts on livelihoods and value chains. Method: A mixed-methods design combined household surveys, focus group discussions, key informant interviews, and postharvest quality measurements; quantitative data were statistically analyzed and qualitative data coded thematically. Practical Applications: Findings inform cooperatives, extension services, and policymakers on targeted training, investment in processing equipment, product diversification, and e‑commerce strategies to improve product value, market reach, and farmer incomes.  Conclusion: Adoption of postharvest technologies and digital marketing improved quality, enabled product diversification, expanded market access, and contributed to higher household incomes; sustained capacity building and infrastructure support are recommended.